A Simple Game Application For Developing Mental Arithmetic For First Grade Elementary Students Using The Challege-Based Learing (CBL) Framework With Swift UI - Nindya Alita Rosalia; Fitri Bimantoro (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2023)
Mathematics is one of the fundamental sciences that underlies the rapid development of technology and knowledge in the present era. Counting is a basic skill that should be acquired and mastered since elementary school. However, the reality is that many first-grade students still struggle with their counting abilities. Some of the problems include lack of motivation for learning, ineffective learning methods, and math phobias. Math phobia refers to a condition where students feel disturbed and stressed when confronted with anything related to mathematics. The factors contributing to math phobia include triggering events, influence from others, and conventional teaching methods in schools. One way to address this issue is by developing students' mental arithmetic skills, as it has been proven to be highly beneficial in shaping their thinking process. Recognizing the potential of utilizing technology, a simple interactive game using Swift UI can be developed to enhance first-grade students' mental arithmetic skills, providing them with an enjoyable learning experience in mathematics.